Understanding the Recognition of Occupational Safety and Health: A Critique of Corporate Culture - Kusmayadi, Yadi; Ronda, Andi Mirza; Seran, Alexander (Indonesian Journal of Social Science Research, 2023)
In the era of globalization, in the face of industrial competition, companies are attempting to instill a culture of Occupational Safety and Health (OSH) as a symbol and image of their existence. However, it is unfortunate that the presence of OSH in the company does not always serve as a barometer of the company's normative compliance with OSH. In practice, the rules governing worker behavior still show varying degrees of permissiveness. The practice of OSH must be accompanied by moral values in order to achieve the desired condition. Therefore, there are two behavioral approaches in OSH communication practices in companies: (1) do the things right, which means following the rules. This does not necessarily resolve OSH problems, as ‘rules’ at the minimum only regulate employee behavior and (2) do the right things, which is moral in nature, which allows workers to act and behave according to their nature because what is outlined in the rules does not always reflect free will, so in the end each worker must find a way to do what’s best. The critical-interpretive approach with phenomenological method in research focuses on the meaning and awareness of OSH caused by communication distortion in the company on workers' behavior towards social reality as something complex, continuously evolving and full of meaning. In the development of Axel Honneth's conceptual dimensions of recognition theory (love, rights and solidarity) has a central role and solution in the distortion of corporate communication, especially in the implementation of OSH programs that emphasize the importance of recognizing worker relationships and developing self-confidence, self-respect and self-esteem, in the context of Good Corporate Governance (GCG) and Governance Risk and Compliance (GRC), recognition theory provides implications for the importance of recognizing workers’ contributions to the goals achieved in the company, thereby increasing workers' dignity and individual values in the company. Without social recognition, OSH will not be able to serve as operational barometer of a start-up company. It will only serve as a framing to protect the company, “as if” it already fulfills its legal obligations towards OSH.